The legend of Diamond Lil : a J. J. Tully mystery - Cronin, Doreen (Balzer + Bray, 2012)
JJ, the search and rescue dog, is ready for a bit of rest and relaxation after solving the mystery of the missing chicks, but there is a new dog next door who is stealing the attention of Moosh and her chicks and the threat of a roaming possum keeps JJ on the alert.